Spectrophotometric Estimation of Abacavir Sulphate in Pharmaceutical Formulations - N. Appala Raju; J. Venkateswara Rao; K. Vanitha Prakash; K. Mukkanti (E-Journal of Chemistry)
Two simple, accurate, rapid and sensitive methods (A and B) have been developed for the estimation of abacavir sulphate in its pharmaceutical dosage form. The method A and B are based on the formation of chloroform extractable complex of abacavir sulphate with bromophenol blue (method A) and bromocresol green (method B), which shows absorbance maxima at 460 nm and 469 nm respectively. The absorbance-concentration plot is linear over the range of 1-10 mcg/mL for method A and B respectively. Results of analysis for all the methods were validated statistically and by recovery studies. The proposed methods are economical and sensitive for the estimation of abacavir sulphate in bulk drug and in its tablet dosage form.